Konstruksi Jender dalam Pertarungan Simbolik di Media Massa - Dinurriyah, Itsna Syahadatud (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2013)
This article examines gender construction in a symbolic dispute in the mass-media that covers euphe–mism and form of censorship. Using critical discourse analysis and hermeneutic, the study concludes that euphe–mism style of male and female in mass media is perceived as a process of shaping and constructing the role patterns of the male and female which then externalized to be a culture. In order to avoid being seen as a violence, gender construction of male and female is done by a variety of styles; changing, neutrallizing the general meaning and defining definition differrently. The form of censorship used by the perpetrator of gender construction in order to maintain the domination is conducted by conceptualizing and reconceptualizing “honor moral” of male and female.Keywords: gender, symbolic struggle, mass media—————————————————————————-Artikel ini membahas konstruksi jender dalam pertarungan simbolik di media massa yang meliputi ben–tuk eufimisasi dan sensorisasi. Dengan memakai analisis wacana kritis dan hermeneutika, studi ini menyimpulkan bahwa gaya eufimisasi laki-laki dan perempuan di media massa disikapi sebagai proses pembentukan peran laki-laki dan perempuan, sehingga tereksternalisasi menjadi suatu kaidah budaya. Agar tidak tampak sebagai suatu bentuk kekerasan, proses konstruksi jender laki-laki dan perem–puan dilakukan dengan menggunakan gaya penggantian, penetralisasian makna umum, dan pendefinisian distingtif. Bentuk sensorisasi yang digunakan pelaku konstruksi jen–der untuk mempertahankan dominasi ialah dengan kon–septualisasi dan rekonseptualisasi “moral kehormatan” laki-laki dan perempuan.Kata Kunci: jender, pertarungan simbolik, media massa